Influence and benefits of using artificial intelligence (AI) in structural health monitoring (SHM) in the commercial airline sector - Costa, Edson (Brazilian Journal of Production Engineering, 2025)
Structural Health Monitoring (SHM) has been attracting the research community in recent decades to enable the design of lighter, safer, and even cleaner aircraft. Therefore, considering that SMH is a critical aspect of the maintenance and safety of an aircraft’s infrastructure, this study sought to explore the growing influence of Artificial Intelligence (AI) on SHM in the commercial aviation sector, showing the main benefits of using AI in this segment. The methodology applied to develop this study was a literature review. The research carried out had an exploratory-descriptive aspect, of a qualitative nature. It was concluded that, with the advancement of digitalization, the volume of data processed by production and maintenance companies is growing and, consequently, the demand for AI to manipulate this data is also growing. AI-based predictive maintenance can help optimize maintenance plans, predict the remaining useful life of components and, consequently, prevent damage.